2018
DOI: 10.1002/asl.855
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the spatial–temporal patterns of droughts in the Brazilian Northeast

Abstract: In Northeast Brazil (NEB), severe droughts have high socioeconomic impacts. In this study, the spatial–temporal characteristics of drought were evaluated based on a new drought index at 4‐km spatial resolution, derived from regional empirical relationships between a remote sensing‐based index and rain‐gauge‐based standardized precipitation index (SPI), a well‐known drought meteorological index. This index was used to compare the spatial pattern of severe drought events (1982–1983, 1992–1993, 1997–1998, and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
25

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 35 publications
3
57
0
25
Order By: Relevance
“…The 2011/2012 hydrological year exhibited the most severe drought condition, and most of the NE was classified as extreme drought and, in some parts of the central semiarid region, as exceptional drought. As shown in previous studies, the recurrent drought events recorded from ending 2011 to 2017 at NE were considered more intense in terms of duration, severity, and recurrence for at least the last 30 years [68][69][70]. This severe drought was associated with an unusual combination of factors.…”
Section: Drought Assessmentmentioning
confidence: 82%
See 1 more Smart Citation
“…The 2011/2012 hydrological year exhibited the most severe drought condition, and most of the NE was classified as extreme drought and, in some parts of the central semiarid region, as exceptional drought. As shown in previous studies, the recurrent drought events recorded from ending 2011 to 2017 at NE were considered more intense in terms of duration, severity, and recurrence for at least the last 30 years [68][69][70]. This severe drought was associated with an unusual combination of factors.…”
Section: Drought Assessmentmentioning
confidence: 82%
“…The 2015/2016 El Niño was one of the strongest on record, comparable to the 1982/1983 and 1997/1998 [73]. Although the large majority of severe drought events in the NEB is associated with the occurrence of El Niño, this is not always the case [70,74], as in the beginning of the multiyear drought in the NE.…”
Section: Drought Assessmentmentioning
confidence: 95%
“…The short-term is less than 6 months, while the long-term is greater than 6 months. According to previous studies, depending on the time scales, SPI can have some relation with the short-term surface moisture conditions associated with agricultural drought [44,45]. Park et al [15] showed that three-month SPI (hereafter referred to as SPI3) had the highest correlation with crop yield, and that oscillations of short-term drought can occur in association with the crop growth period [20].…”
Section: Meteorological Drought Indexmentioning
confidence: 99%
“…Precisase entender as diferenças entre os eventos extremos de tempo e de clima. Na região Nordeste do Brasil, o fenômeno climático que causa os maiores prejuízos à população, especialmente a do semiárido, é a seca, que varia em intensidade, magnitude e frequência (Cunha et al, 2015;Cunha et al, 2018;Marengo et al, 2018;Alvalá et al, 2017;. Eventos extremos de tempo estão relacionados à mudanças repentinas das condições meteorológicas em um dia, como enchentes causadas por fortes temporais , ou a um curto período de tempo, como ondas de calor ou frio (Geirinhas et al, 2017).…”
Section: Introductionunclassified